السلوك المتصنع وعلاقته ببعض المتغيرات لأمهات أطفال الرياض - علوان علا حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The current study aimed to identify the level of pretentious behavior among mothers of kindergarten children, and to know the relationship between pretentious behavior and some variables among mothers of kindergarten children. The researcher relied on a measurement (Alwan,2015) to measure the pretentious behavior of mothers. The was applied to a sample of mothers amounting to 235mothers who were selected according to the simple random sampling method from the Second Karkh Baghdad Education Directorate, and after processing the data using appropriate statistical methods, then Reaching conclusions, recommendations and proposals.